Pengaruh Karakteristik Kewirausahaan terhadap Keberhasilan Usaha UMKM Perempuan di Gunungkidul - Sulasmi, Sulasmi; Susilowati, Nenden; Handayani, Titin Hera Widi (STKIP PGRI SITUBONDO, 2024)
The Impact of Entrepreneurial Characteristics on Business Success of Women MSMEs in Gunungkidul Abstract: The study aims to identify women's entrepreneurial characteristics and analyze their influence on their business success. This research explores the influence between entrepreneurial characteristics of confidence, risk-taking, and leadership on business success. This research method uses a survey with a quantitative approach. The research design is explanatory research. The data collection technique used a structured questionnaire with a Likert scale. The sampling technique used stratified random sampling based on business type. This research involved 30 female MSME players in Semanu Village, Gunungkidul. Multiple regression analysis to test the effect of entrepreneurial characteristics of confidence, risk-taking, and leadership on business success. Data analysis using SmartPLS. The results showed that leader entrepreneurial characteristics have the strongest and most significant influence on business success with a coefficient of 0.418, while confident entrepreneurial characteristics have a moderate influence with a coefficient of 0.208 on business success and risk-taking entrepreneurial characteristics have a small influence on business success with a coefficient of 0.116. Leadership characteristics are the strongest factor influencing business success, followed by self-confidence, and finally by risk-taking. Keywords: entrepreneurial characteristics, leadership, business success.